Elevating community voices through inclusive science communication: a case study of the We are Water program in the Southwestern United States - Marsh, Casey L.; Gold, Anne U.; Rongstad Strong, Brigitta (Frontiers in Communication, 2023)
Science communication plays a pivotal role in cultural engagement and life-long science learning. However, historically marginalized communities remain undervalued in these efforts due to practices that prioritize specific individuals, such as those who are affluent, collegeeducated, able-bodied, and already scientifically engaged. Science communicators can avoid these practices by acknowledging the intersecting historical and cultural dimensions surrounding science beyond those of the majority culture and practicing inclusive science communication efforts. Here, we define and describe the importance of inclusive science communication and outline how we use an asset-based community engagement framework in a place-based education program's communication practices with rural communities in the Southwestern United States. We describe how we designed our communication spaces, found our voice, and effectively communicate with non-English speaking and bilingual communities. We provide examples from the We are Water program, demonstrating how we utilize inclusive science communication practices to engage more widely with diverse communities and create space for community voices to be heard and shared. We conclude that the use of inclusive science communication strategies and an asset-based community engagement framework has allowed the We are Water program to connect with rural communities while communicating in a way that elevates historically marginalized voices, creates space for communities to share their own experiences through memories and stories, and honors diverse perspectives and ways of knowing.